Biofunctionalized liquefied capsules as three dimensional basement membranes to promote vascularization and tissue integration - Passos, Catarina Tonini (2025)
In the last years, liquid-core microcapsules composed by a permselective polyelectrolyte membranes have been successfully explored as self-regulated compartmentalized biosystems for bone and cartilage regeneration, allowing the confinement of biological cargo while enabling the diffusion of essential molecules for cell survival. Taking the advantage of the unique liquefied environment, we propose a novel design of capsule-shaped membranes that could mimic the composition, structure and biofunctions of the in vivo basement membrane. Basement membranes are a type of extracellular matrix present between epithelial or endothelial and connective tissues. This highly conserved network, composed mainly by laminin and type IV collagen connected by nidogen, heparan sulfate proteoglycans and other molecules, functions as a natural scaffold for tissue formation, compartmentalizing and providing mechanical support for the surrounding cells as well as modulating their behaviour through sequestrating/releasing key molecules. Inspired on the natural biochemical and biophysical properties of the in vivo basement membrane, liquid-core microcapsules composed by a basement membrane protein multilayered shell were successfully constructed by resorting to electrohydrodynamic atomization for the production of the alginate templates and layer-by-layer technique to assembly type IV collagen and laminin buildingup the basement membrane shell. These mimetic-like capsule-shaped membranes have shown to act as a permselective barrier allowing diffusion of nutrients and other essential molecules, while preventing cell migration due to their larger size. Apart from physical barrier and compartmentalized functions, these biomimetic compartmentalized systems have exhibited interwoven nanofibrous networks that supported cell attachment. We foresee the application of these 3D capsule-shaped basement membranes as contributors to angiogenesis and vascularization approaches as well as in vitro screening models.